AI AND DIGITAL TRANSFORMATION 4.0: THE ROLE OF AI AND DIGITAL TRANSFORMATION IN PROMOTING SUSTAINABLE CONSUMPTION (Marketing Journal, 2025)
The convergence of artificial intelligence and digital transformation technologies presents unprecedented opportunities to reshape consumer behavior toward sustainability. This article examines how AI-driven solutions enable personalized environmental impact tracking, optimize resource allocation, and facilitate transparent supply chains. Through analysis of current implementations and empirical evidence, this research demonstrates that Industry 4.0 technologies serve as powerful catalysts for the transition toward a circular economy and responsible consumption paradigm, while acknowledging critical challenges including digital divides, rebound effects, and energy consumption concerns.